Quality of antiretroviral and opportunistic infection medications dispensed from developing countries and Internet pharmacies. (10th November 2014) - Wang, Ting; Hoag, Stephen W.; Eng, Maria L.; Polli, James; Pandit, Neha Sheth
Summary What is known and objective Generic manufacturers help decrease the cost of antiretroviral (ARV) and antimicrobial medications which are used to treat opportunistic infections (OIs) in developing countries. Concerns have been expressed about potential quality issues with such medications as a result of the identification of numerous counterfeit medications in developing countries. However, few studies have assessed the quality of these medications using the United States Pharmacopeia (USP) compendial standards. The goal of this study was to assess the quality of ARV and OI medications obtained from various sources, including South Africa, United States, China, Ethiopia, Thailand, Laos, Mexico, Nigeria and five Internet pharmacies. Methods Zidovudine, lamivudine, efavirenz, nevirapine, isoniazid and sulfamethoxazole/trimethoprim tablets/capsules were obtained from eight countries and five Internet pharmacies. The tablets/capsules were separated into distinct samples, based on the drug's active ingredient, manufacturer and drug control number. Each distinct sample was analysed for drug content, dissolution, content uniformity and breaking force using USP 32‐National Formulary 27 (USP 32‐NF 27) compendial methods and compared to the USP standards. Results and discussion A total of 2027 tablets/capsules were obtained with 88 distinct samples identified. All samples met the USP 32‐NF 27 standards for drug content with a range of 92·7–108·6%. Six of the 88 samples failed the dissolution test by 1·5–8·3% below the standard range. Ninety‐eight per cent of all 88 samples met the USP criteria for content uniformity based on weight variation. One sample of isoniazid was found to have a low breaking force of 2·8 kiloponds. The results of this study show that there were no problems with the samples of ARV and OI medications tested for drug quality from the specified locations. As there are many studies and reports that discuss the poor quality of generic medications with only a few assessing drug quality, the implications of this study's results are to: (i) help better understand patient outcomes; (ii) help patients gain access to beneficial medications for HIV and OIs; and (iii) ensure an overall increase in access to medications where needed. What is new and conclusion This study is one of the largest to date concerning medication type and sample size for the assessment of ARV and OI medications using drug content as a measure of quality. The samples were obtained from more diverse geographical locations compared to previous studies and, for the first time, included Internet pharmacies. In addition to drug content, this study evaluated a more complete quality profile including dissolution, content uniformity and breaking force. This study showed that drug quality should be assessed consistently in order to better identify counterfeit medications compared to current assessments and that there should be uniform guidelines for how to assess quality.